2015
DOI: 10.1111/rda.12654
|View full text |Cite
|
Sign up to set email alerts
|

The Recipients' Parity Does Not Influence Their Reproductive Performance Following Non‐Surgical Deep Uterine Porcine Embryo Transfer

Abstract: With the development of the non-surgical deep uterine (NsDU) embryo transfer (ET) technology, the commercial applicability of ET in pigs is now possible. There are, nevertheless, many factors that influence NsDU-ET effectiveness that need to be addressed. The aim of this study was to evaluate the effects of the weaned recipients' parity on fertility and prolificacy following NsDU-ET. The recipients (n = 120) were selected based on their reproductive history and body condition and grouped into three categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…Multiparous sows are ideal as recipients because the insertion of the NsDU‐ET catheter is easier, their conduct during the transfers is better (Martinez, Cuello et al., ), and their oestruses are naturally and effectively synchronized by managing weaning. All of the abovementioned observations led us to evaluate the influence of recipient parity (parity 1 to 5) on NsDU‐ET outcomes (Martinez, Nohalez et al., ). The results indicated that neither the efficiency of the NsDU‐ET procedure nor the reproductive performance of the recipients were affected by parity.…”
Section: Factors Affecting the Et Technologymentioning
confidence: 99%
“…Multiparous sows are ideal as recipients because the insertion of the NsDU‐ET catheter is easier, their conduct during the transfers is better (Martinez, Cuello et al., ), and their oestruses are naturally and effectively synchronized by managing weaning. All of the abovementioned observations led us to evaluate the influence of recipient parity (parity 1 to 5) on NsDU‐ET outcomes (Martinez, Nohalez et al., ). The results indicated that neither the efficiency of the NsDU‐ET procedure nor the reproductive performance of the recipients were affected by parity.…”
Section: Factors Affecting the Et Technologymentioning
confidence: 99%
“…These data, together with the excellent fertility results following NsDU-ET [2][3][4][5][6], suggest that the insertion of the catheter does not cause significant damage to the cervix and/or uterine horn. The results of the present study parallel earlier studies and reinforce the suggestion that NsDU-ET is a non-invasive and welfare-preserving technology.…”
Section: Discussionmentioning
confidence: 74%
“…Secondly, the use of recipient sows was preferred because weaning is a physiological, regular and outstanding process that facilitates estrus synchronization in swine [19]. Thirdly, the parity of the recipient does not affect the success of NsDU-ET [6] and finally, the use of recipient sows with a wide parity range facilitates the scheduling of ET in the recipient farms due to the higher availability onfarm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for surgical ET has certainly hampered the progress of bringing this method closer to implementation under field conditions. Multiple research groups have attempted to develop a nonsurgical ET procedure (Galvin et al, 1994;Hazeleger and Kemp 1994;Li et al, 1996;Yonemura et al, 1996;Martinez et al, 2004;Martinez et al, 2016).…”
Section: Embryo Transfer In Sowsmentioning
confidence: 99%